Small changes in the activity of chloroplastic NADP(+)-dependent ferredoxin oxidoreductase lead to impaired plant growth and restrict photosynthetic activity of transgenic tobacco plants - Sonnewald, Uwe; et al. (Plant Journal, 2002)
A ferredoxin-NADP(+) oxidoreductase (FNR) cDNA from tobacco (Nicotiana tabacum cv. Samsun) was cloned and sequenced. Comparison of the deduced amino acid sequence revealed high identity to FNR proteins from Capsicum annuum, Pisum sativum, Spinacia oleracea and Vicia faba. Transgenic tobacco plants were generated that constitutively express the FNR cDNA in reverse orientation between the CaMV 35S promoter and the polyadenylation signal of the octopine synthase gene. Plants expressing the FNR antisense gene showed lower levels of FNR mRNA and protein accumulation, which was paralleled by a decrease in FNR activity. As a consequence, NADPH levels declined whereas NADP(+) levels increased, leading to an unaltered NADP(H) pool. Growth rates, chlorophyll content and net CO2 uptake rates at high and low irradiances were strongly reduced in FNR antisense tobacco plants. These changes were accompanied by an over-reduced state of P-700 as estimated by absorption changes at 820 nm. FNR control coefficients determined for the photosynthetic rate at saturating (C-R = 0.94) and limiting (C-R = 0.70) light conditions revealed a prominent role of this reductase in the regulation of photosynthesis.
Keywords: photosynthesis; ferredoxin-NADP(+) oxidoreductase; antisense; transgenic tobacco plants; control coefficient